ANALISIS USAHA TANI SINGKONG DITINJAU DARI WILAYAH DI “ CV RIANTO BASUKI” DESA BANDAR SAKTI KECAMATAN TERBANGGI BESAR LAMPUNG TENGAH - Antik Suprihanti; Nanik Dara Senjawati; Andriyanto Hari Prastiya (Jurnal Dinamika Sosial Ekonomi, 2009)
Analysis of cassava’s Farming Observed from Aspect of Area in CV Rianto Basuki Desa Bandar Kecamatan Terbanggi Lampung Tengah. The objective of research is to know how much the price of cassava’s selling to the factory of cassava’s farming is; to know the production resulted based on the areas, to know profit and afficincy produced of cassava farming held between the north and south areas, and for analyze productivity of cassava’s farming held between the not and south areas. The research uses decriptive method. The research method uses case method. The analysis is used to know profit and efficiency produced of cassava farming held between the north and south areas using t test statistic analysis. The result of this research showed that the price of cassava’s selling in the north area is 635/kg and in the south area is 550/kg. Production resulted in the north area is 45.833,33 kg/ha and in the south area is 35. 666, 67 kg/ha.  Profit and effciency produced in the north area is higher than those the south area. it can be seen by the price of profit in the north area is Rp 157. 086. 933,33 and the profit in the south area is 2,20 and the efficiency per wide range of farming in the south area is 1,34. Productivity in the north areas is 45, 83 ton/ha and the productivity in the south area is 35, 67 ton/ha.Keywords:  Cassava;s farming, Profit, Efficiency and productivity